2021
DOI: 10.1186/s12871-021-01249-1
|View full text |Cite
|
Sign up to set email alerts
|

Time- and dose-dependent correlations between patient-controlled epidural analgesia and intrapartum maternal fever

Abstract: Background To investigate the relationship between intrapartum maternal fever and the duration and dosage of patient-controlled epidural analgesia (PCEA). Methods This observational study included 159 pregnant women who voluntarily accepted PCEA. During labor, patients with body temperature ≥ 38 °C were classified into the Fever group, (n = 42), and those with body temperature < 38 °C were classified into the No-fever group (n = 117). The outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…This implies a lack of correlation between ERMF and neonatal hypoxia. Other studies conducted by our group ( 13 ) have also yielded similar results.…”
Section: Discussionsupporting
confidence: 87%
“…This implies a lack of correlation between ERMF and neonatal hypoxia. Other studies conducted by our group ( 13 ) have also yielded similar results.…”
Section: Discussionsupporting
confidence: 87%
“…The finding that reducing the dose of local anaesthetic administered by epidural analgesia may reduce the incidence of intrapartum fever is supported by the results of observational studies reporting time- and dose-dependent correlations between epidural analgesia and intrapartum fever development. 88 Further studies have also supported the association between duration of epidural analgesia and development of intrapartum fever. Lieberman and colleagues 89 observed that amongst women who received an epidural the incidence of fever increased from 7% for labours <6 h to 36% for labours >18 h, and Yin and Hu 90 observed that labouring <6 h with epidural analgesia did not increase the risk of fever development, but that risk did increase significantly when epidural analgesia lasted >6 h. This evidence supports the concept that total local anaesthetic dose plays an important role in the mechanism of intrapartum fever development, as the longer an epidural is in situ , the higher the dose received.…”
Section: Discussionmentioning
confidence: 90%
“…Labour analgesia can effectively relieve pain and improve the success rate of vaginal delivery. However, during childbirth, women may have fever, and the probability of fever in women who choose labour analgesia is significantly higher (Viscomi & Manullang, 2000; Zhao et al, 2021). This study found that the incidence of maternal intrapartum fever in women undergoing epidural analgesia was 27.55%.…”
Section: Discussionmentioning
confidence: 99%